Stress evolution of GaN/AlN heterostructure grown on 6H-SiC substrate by plasma assisted molecular beam epitaxy - Agrawal, Manvi (2017)
The stress evolution of GaN/AlN heterostructure grown on 6H-SiC substrate by plasma assisted molecular beam epitaxy (PA-MBE) has been studied. AlN nucleation layer and GaN layer were grown as a function of III/V ratio. GaN/AlN structure is found to form buried cracks when AlN is grown in the intermediate growth regime(III/V∼1)and GaN is grown under N-rich growth regime (III/V<1). The III/V ratio determines the growth mode of the layers that influences the lattice mismatch at the GaN/AlN interface. The lattice mismatch induced interfacial stress at the GaN/AlN interface relaxes by the formation of buried cracks in the structure. Additionally, the stress also relaxes by misorienting the AlN resulting in two misorientations with different tilts. Crack-free layers were obtained when AlN and GaN were grown in the N-rich growth regime (III/V<1) and metal rich growth regime (III/V≥1), respectively. AlGaN/GaN high electron mobility transistor (HEMT) heterostructure was demonstrated on 2-inch SiC that showed good two dimensional electron gas (2DEG) properties with a sheet resistance of 480 Ω/sq, mobility of 1280 cm^2/V.s and sheet carrier density of 1×10^13 cm^−2.